2017
DOI: 10.3892/etm.2017.4276
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of choline against hypoxia-induced injuries of vessels and endothelial cells

Abstract: The current study aimed to lay a theoretical foundation for further development of choline as an anti-hypoxia damage drug. Wild-type, 3- to 5-month-old male Sprague-Dawley rats, weighing 180–220 g, were used in this study. The rats were randomly divided into a normoxic control group (n=16) and a chronic intermittent hypoxia (CIH) group (n=16). The effects of CIH on acetylcholine (ACh)-mediated endothelium-dependent vasodilatation in the rat cerebral basilar arterioles and mesenteric arterioles, as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Cells were cultured in the normal condition and treated with different doses of Dox (0–100 µg/mL) at 37ºC for 24 h. The twenty μL MTS solution (Sigma) was added per well and incubated at 37ºC for 3 h. Finally, optical density (OD) was measured under the 492-nm wavelength, and the survival rates were calculated. 18…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were cultured in the normal condition and treated with different doses of Dox (0–100 µg/mL) at 37ºC for 24 h. The twenty μL MTS solution (Sigma) was added per well and incubated at 37ºC for 3 h. Finally, optical density (OD) was measured under the 492-nm wavelength, and the survival rates were calculated. 18…”
Section: Methodsmentioning
confidence: 99%
“…Cells were cultured in the normal condition and treated with different doses of Dox (0-100 mg/mL) at 37ºC for 24 h. The twenty mL MTS solution (Sigma) was added per well and incubated at 37ºC for 3 h. Finally, optical density (OD) was measured under the 492-nm wavelength, and the survival rates were calculated. 18 Chick chorioallantoic membrane (CAM) tumor formation assay CAM in chicken embryo has been identified as an immune-deficient host model for tumor formation in vivo. [19][20][21][22] In order to inoculate cells onto the CAM, on day 3 (starting from the day of hatched chicken egg incubation), 2-mL albumin was withdrawn and a window was opened in the shell with an electric drill equipped with a 0.75-inch wheel tip (Dremel Moto-Tool; Emerson Electric Co., USA).…”
Section: Mts Assaymentioning
confidence: 99%
“…Nicotine receptors stimulated with ACh in inflammatory cells inhibit the release of pro-inflammatory cytokines in a concentration-dependent manner [ 22 ]. It has also been reported that choline is involved in cell damage and metabolism, protects against hypoxia-induced injuries of vessels and vascular endothelial cells [ 23 ], and is essential for tissue repair after injury [ 24 ].…”
Section: Choline In Dry Eye Syndrome and Ocular Surfacementioning
confidence: 99%
“…Numerous investigations have provided evidence that a hypoxic environment can induce oxidative stress (Ramanathan et al, 2005 ; Niki, 2010 ; Yan et al, 2019 ), apoptosis (Li et al, 2007 ; Leszczynska et al, 2015 ), inflammation (Yang et al, 2013 , 2015 ; Koh et al, 2015 ), autophagy (Xu and Zhang, 2011 ; Yang et al, 2015 ) and Ca 2+ overload (Zhao et al, 1999 ) among other deleterious effects. Therefore, efforts are underway to develop new strategies to attenuate or prevent the damage caused by hypoxia, and there has been recent interest in the use of alternative medicines to antagonize hypoxia-induced tissue damage, such as aminophylline (Yang et al, 2007 ) diazepam, dexamethasone (Gong et al, 2015 ), choline (Zhang et al, 2017 ) and Rhododendron simsii Planch flower (Guo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%